2016
DOI: 10.1016/j.actatropica.2015.10.013
|View full text |Cite
|
Sign up to set email alerts
|

A rapid molecular diagnosis of cutaneous leishmaniasis by colorimetric malachite green-loop-mediated isothermal amplification (LAMP) combined with an FTA card as a direct sampling tool

Abstract: Leishmaniasis remains one of the world's most neglected diseases, and early detection of the infectious agent, especially in developing countries, will require a simple and rapid test. In this study, we established a quick, one-step, single-tube, highly sensitive loop-mediated isothermal amplification (LAMP) assay for rapid detection of Leishmania DNA from tissue materials spotted on an FTA card. An FTA-LAMP with pre-added malachite green was performed at 64 degrees C for 60 mm using a heating block and/or wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 17 publications
1
45
0
1
Order By: Relevance
“…Implementing a molecular technique such as qPCR for field work in endemic areas for leishmaniasis leads to having a special infrastructure as well as the acquisition of costly equipment and reagents (its cost is reported to be up to three times higher than that of conventional PCR) (Bock and Langer, 1993). This reflects the need to develop new technologies more sensitive but easy to acquire and to be implemented in this type of regions, such as LAMP (Notomi et al, 2000; Tomita et al, 2008; Nzelu et al, 2014, 2016; Abbasi et al, 2016) and nanoparticles (Andreadou et al, 2014). Although microscopy remains the gold standard for routine diagnosis, the high incidence of CL in different regions of South America highlights the need to rethink the implementation of specific strategies for the correct and timely diagnosis of this disease.…”
Section: Discussionmentioning
confidence: 99%
“…Implementing a molecular technique such as qPCR for field work in endemic areas for leishmaniasis leads to having a special infrastructure as well as the acquisition of costly equipment and reagents (its cost is reported to be up to three times higher than that of conventional PCR) (Bock and Langer, 1993). This reflects the need to develop new technologies more sensitive but easy to acquire and to be implemented in this type of regions, such as LAMP (Notomi et al, 2000; Tomita et al, 2008; Nzelu et al, 2014, 2016; Abbasi et al, 2016) and nanoparticles (Andreadou et al, 2014). Although microscopy remains the gold standard for routine diagnosis, the high incidence of CL in different regions of South America highlights the need to rethink the implementation of specific strategies for the correct and timely diagnosis of this disease.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, several authors have combined the LAMP technique with FTA cards (Flinders Technology Associates) that protect the nucleic acids from oxidation, nucleases and UV damage at room temperature for long storage periods for the diagnosis of leishmaniasis. In this sense, Nzelu et al, 2016 have developed a one-step, single-tube, highly sensitive LAMP assay for rapid detection of Leishmania DNA from tissue spotted on an FTA card, which has incorporated malachite green for the final visualisation step. The validation of this system was carried out on tissue samples obtained by aspirating or scraping the lesions of CL patients from Peru.…”
Section: Lamp Assays For Diagnosis Of Leishma-niasismentioning
confidence: 99%
“…The validation of this system was carried out on tissue samples obtained by aspirating or scraping the lesions of CL patients from Peru. The developed system was fast (30 min), sensitive (detection levels as low as 0.01 parasites/µl) and specific (without cross-reactivity with the genomic DNA of Trypanosoma cruzi, Trypanosoma brucei gambiense, human and dog) [91].…”
Section: Lamp Assays For Diagnosis Of Leishma-niasismentioning
confidence: 99%
“…The study showed that LAMP was efficient to detect 10 1 copies of DNA. They concluded that the newly developed LAMP was helpful when leishmania parasite density is very low, especially during the early infection stage (Nzelu et al 2014(Nzelu et al , 2016. There was a number of other reported significant practices of LAMP including Trichomonas viganalis (Reyes et al 2014), Necator americanus (Mugambi et al 2015) and Strongyloides stercoralis (Watts et al 2014), and it was shown that LAMP is at least 1000 times more sensitive than the conventional PCR.…”
Section: B3cmentioning
confidence: 99%
“…Other dyes such as malachite green dye (Sriworarat et al 2015;Lucchi et al 2016;Nzelu et al 2016), Picogreen dye (Batra et al 2015), Gelred dye (Wozniakowski et al 2013;Wassermann et al 2014), SYTO fluorescent dye (Liu et al 2013;Watts et al 2014;Mwendwa et al 2017) Zhou et al, 2014). The reaction between free calcein and magnesium ions intensified the fluorescence of LAMP product (ii.)…”
Section: Lamp End-point Detection Methodsmentioning
confidence: 99%